ANALISIS BAURAN PEMASARAN TERHADAP PENJUALAN USAHA BAKERY (Studi Kasus pada Toko BreadTalk dan Kawan Baru Manado) - Lourina Sondakh (AGRI-SOSIOEKONOMI, 2012)
The object of the research is Bakery shops in Manado. Bread Talk and Kawan Baru Bakery shop have chosen to be observed. The purpose of this study is to determine and to compare the marketing mix that is used by both bakery shops. The study is expected to provide input for bakery manufacturers in terms of management. From these results it can be concluded that the concept of marketing mix of Kawan Baru bakery shop is the selling concept that the output is profit while Bread Talk bakery shop is not only profit but also consumer satisfaction. The difference between the two stores is in the application of 4P indicators which are product, price, place and promotion.Keywords: Marketing Mix, Bakery Shops